Characterization of Small-Scale Fishing Activity in Luanda Bay (Angola) - Faria, Silvana; Macuéria, Marisa; Mosley, Benjamin A.; Teodósio, M. Alexandra; Baptista, Vânia (Journal of Tourism, Sustainability and Well-being, 2021)
Luanda Bay, the second largest bay and one of the most important ecosystems of the Angolan coast, supports many human activities. This bay supports a range of marine biodiversity that serves as a means of livelihood and source of income for more than fifty small-scale artisanal fisheries and collectors of worms and bivalve molluscs. The present study is the first record of this fishing activity in Luanda Bay and the objective was to characterize the resource exploitation in this bay based on field data obtained by distributing self-reported and structured questionnaires to the two fishing communities (fishermen and shellfish harvesters) in Luanda Bay: Luanda Island and Luanda Commercial Harbour. The results revealed that the two fishing communities used different vessel types during fishing activity. In the Luanda Island fishing community, the fishermen used rowboats (“Chata”) and motorboats, and in the Commercial Port of Luanda fishing community, they used an adapted vessel made of Styrofoam boards. The main gears were line/hooks (34.1%), shovel (25.0%), seine (9,1%), gillnet (6.8%), trawl (4.5%) and traps (2.3%). According to the local fishing communities, Pomadasys jubelini, Mugil cephalus, Dentex spp., Senilia senilis, Mactra glauca, Donax spp., Perna perna, and Lucinella divaricata were the predominant species. In relation to the earnings by fishing day, the Luanda Island community had a higher income (average: 14.4 ± 8.3 euros; maximum: 39.0 euros) than Luanda Commercial Harbour community (average: 8.4 ± 5.1 euros; maximum: 24.2 euros). Thus, the quality of life of the fishing communities seems to be highly depending on this activity.